أثر الشمول المالي الرقمي على النمو الاقتصادي دراسة قياسية لعينة من الدول الآسيوية : Impact of digital financial inclusion on economic growth Standard Study of a sample of Asian countries - طهراوي دومة علي; بسبع عبد القادر; بوخاري خيرة (Journal of North African Economies, 2025)
This research aims to measure and analyze the impact of digital financial inclusion on the economic growth of a sample of Asian countries (Indonesia, Malaysia, India, Pakistan and Turkey), where the descriptive and analytical approach was relied on to suit the subject of research and the standard approach using the self-regression model of time gaps distributed on the PANEL-ARDL cross-sectional data,and based on this, the study found a positive long- and short-term relationship between the two variables, and that the increase In the value of the financial inclusion index in one unit, which leads to a change in the rate of economic growth by 0.29 units, and the results of causality tests found a two-way causal relationship between the index of digital financial inclusion and economic growth in the sample of countries studied during this period, Countries also depend on launching financial services that include the use of digital technologyincluding the use of mobile phones, payments and others, had a positive impact on inclusion. Financial and economic growth.